Tourism Attractions and Services Development of Siring Tendean Tourist Attraction in Banjarmasin City - Suriyani, Erna (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to determine the tourist attraction and service development of the Tendean Riverwalk tourist attraction in Banjarmasin City. This is a descriptive study with a qualitative approach, and data collection was carried out through observation, interviews, and documentation. The results of the study show that visitors come to the Tendean Riverwalk tourist attraction because of the attraction's appeal. The attractions of the Tendean Siring tourist site include the floating market, which has unique activities carried out by the traders that represent the local culture of Banjarmasin City. The uniqueness of the river tour, the observation tower, and the Bekantan statue, which is the mascot of Banjarmasin City and an animal native to Kalimantan, also contribute to the site's appeal. Its open location and easy accessibility for visitors are additional factors.The Banjarmasin City Government has provided services to develop this tourist attraction by building infrastructure or facilities, but these are not yet optimal. There are several shortcomings, particularly regarding safety issues on river tours, lack of lighting at night, cleanliness of public facilities in the Siring Tendean area, and cleanliness of the river in terms of trash and vegetation that detracts from the beauty of the tourist attraction, as well as lack of maintenance of the proboscis monkey statue. Therefore, it is recommended that the Banjarmasin city government and tourist attraction managers continue to pay greater attention and provide better services, especially by completing the facilities to support the Siring Tendean tourist attraction.